The power of e-government: technical, discursive, human - Henman, Paul (Politik, 2012)
Governments make extensive use of the internet and other digital technologies for administering govern- ment, delivering services and supporting political processes. All these activities are embraced by the term ‘e-government’. Yet many perceive digital technologies as mundane administrative tools simply deployed by government actors. In contrast, this paper argues that the eld of e-government is infused by power and has power e ects. Drawing on recent theoretical thinking of power, the paper articulates and examines three distinct, but inter-twined, dimensions of the power of e-government: technical; discursive; and human. ese dimensions are illustrated using previously published empirical e-government research. e paper observes that digital technologies have power e ects that over ow the intentions of their designers and deployers. At the same time, the technical capacities of digital technologies do not determine their power e ects, as they are inserted within and become entangled with the operation of human power. Any understanding of the dynamics of e-government must therefore give attention to this complex interplay of the multiple dimensions and actors of power.